Upaya Meningkatkan Aktivitas dan Prestasi Belajar Matematika Melalui Penerapan Metode Permainan Di Kelas VI SD Negeri 327 Sinunukan Kecamatan Sinunukan - Torang Siregar (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2023)
The results of observations in the classroom when mathematics learning was taking place, class VI students tended to be passive and students' mathematics learning activities were very lacking. For mathematics lessons, the average score obtained by class VI students in the weight measurement material, which was the material before this research was carried out, was 50.37 and the percentage of students who reached the learning completion standard was 33.33%. This value is very far from the percentage of students who reach the teaching and learning completion standards (SKBM) set at SD Negeri 327 Sinunukan, which is 60%. This classroom action research (PTK) was carried out for 2 months using the game method in an effort to increase the mathematics learning activity and performance of class VI students at SDN 327 Sinunukan, Sinunukan. The research was carried out in two cycles, each consisting of two meetings through the following stages: planning, observation and reflection. The data collection technique is carried out through observation sheets at each meeting by observers to see data about learning activities, while data about learning outcomes is obtained through daily test scores and student mathematics learning achievements in cycle 1 and cycle 2. Results obtained from Classroom Action Research (PTK ) through the game method model, shows an increase in student activity results, especially activities for preparing places, materials and tools by 55.56%, activities to express ideas by 66.67% and reading game rules and books by 74.04%. %. Based on data on student mathematics learning achievement, the class average score in cycle I was 69.62, increasing to 73.51 in cycle II. The percentage of students who achieved the completion standard also increased in cycle I by 88.88% (Good Category), increasing to 100% (Special Category) in cycle II.